PENGARUH GREEN STRATEGY DAN GREEN INVESTMENT TERHADAP CARBON EMISSION DISCLOSURE DENGAN MEDIA EXPOSURE SEBAGAI VARIABEL PEMODERASI - Ramadhani, Kamila; Astuti, Christina Dwi (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2023)
This study aims to examine the effect of Green Strategy and Green Investment on Carbon Emission Disclosure with Media Exposure as a Moderating Variable. This study uses secondary data obtained from sustainability reports and annual reports. The research population is in the energy sector, the transportation and logistics sector, the infrastructure sector, and the basic materials sector from 2019 – 2021 with purposive data analysis for sampling technique, and sample companies in this research were 300 companies and there were 10 outlier data, so the total observation data in this research was 290 companies.  . The data analysis technique used in this research is multiple linear analysis. Further research is suggested to add independent variables that affect disclosure of carbon emissions such as environmental management system and green intellectual capital or expand the corporate sector used in conducting this research such as non-cyclical consumers, cyclical consumers, and technology. The results obtained from this study are that the influence of the green strategy has a positive effect on carbon emission disclosure. The effect of green investment has no positive effect on carbon emission disclosure. Media exposure is able to strengthen the effect of green investment on carbon emission disclosure, but is unable to strengthen the effect of green strategy on carbon emission disclosure